PENCEGAHAN COVID-19 PADA IBU HAMIL DENGAN VAKSINASI - Fitria Edni Wari; Farida Yuliani; Erfiani Mail (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2022)
Coronavirus 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARSCoV-2) has been worrying the world since its first appearance. Although the absolute risk for maternal morbidity and mortality is low, pregnancy remains a risk factor for hospitalization, ICU admission, and COVID-19-related extracorporeal membrane oxygenation requirements compared to nonpregnancy. Protection of pregnant women from SARS-CoV-2 infection is very important to reduce maternal morbidity and mortality. Vaccination is the most promising method to control the spread of COVID-19. This descriptive study aims to determine the description of pregnant women who are vaccinated against covid-19, with the population who perform pregnancy checks at the Gayaman Health Center, Data collection was carried out in April 2022, using a questionnaire that was given directly to respondents and still complied with health protocols. Sampling by total sampling where 36 pregnant women were obtained who did prenatal check-ups and completed the questionnaire. The results of the study Most of the respondents had received the covid-19 vaccine, namely 31 respondents (86.11%). Health workers still have to provide information regarding the importance of covid-19 vaccination for pregnant women so that the coverage of COVID-19 vaccination for pregnant women can be increased.